Analysis Absorbed Dose Sensitivity of 18F-FDG to Abdominal Organ Mass Variation Using MIRDcalc - Ramacos Fardela; Ufairah Mahadisa Rizanov; Sofia Sogita; Muhammad Ilyas; Alhaj Saidi Akasah; Latifah Aulia Rasyada (Universitas Nurul Huda, 2026)
18F-fluorodeoxyglucose Positron Emission Tomography (PET) using ¹⁸F-fluorodeoxyglucose (¹⁸F-FDG) is widely used in nuclear medicine. Accurate estimation of organ absorbed dose is important for patient safety and protocol optimization. However, standard dosimetry methods based on reference computational phantoms may not fully represent individual anatomical variability, particularly organ mass differences that influence absorbed dose estimation.This study aimed to analyze the sensitivity of absorbed dose to abdominal organ mass variations for ¹⁸F-FDG. A computational dosimetry simulation study was performed using MIRDcalc and the ICRP 133 adult male reference phantom to evaluate simultaneous mass variations of six abdominal organs within a ±50% range. A quadratic relationship was found between mass change and average absorbed dose (R²=0.9928). Dose decreased by 8.5% at +20% mass and increased by 9.2% at −20% mass. The small intestine showed the highest sensitivity (S=−0.45). Organ mass variation substantially influences absorbed dose estimates in simulation-based ^18F-FDG dosimetry. Further studies incorporating patient imaging data are required for clinical validation.